Representasi Pola Asuh Demokratis pada Film “Keluarga Cemara 2” - Fernanda, Dede Yogi; Dwivayani, Kadek Dristiana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The social phenomenon of conflict in the family between younger siblings and older siblings is rampant, especially in Indonesian society, therefore if there is no prevention done through proper parenting, the phenomenon of conflict in the family will continue. The rise of family conflict cases in Indonesia has led many directors to raise this phenomenon in a film. One of the Indonesian films that represent parenting and family conflict is Keluarga Cemara 2. This research aims to find out how the representation of democratic parenting is shown in Keluarga Cemara 2. The research method used in this research is interpretative qualitative with the Roland Barthes semiotic analysis method which sees meaning through the denotation, connotation and myth stages. The results of this study are shown based on seven scenes selected by the researcher. The denotation meaning in this film represents democratic parenting with controlled freedom, direction from parents and rules and attention through the use of verbal and non-verbal language. The connotation meaning in this film is the importance of choosing the right parenting, which shows the importance of establishing good communication, openness and mutual understanding that makes conflicts in the family can be resolved properly. The mythical meaning contained in the film Keluarga Cemara 2 is that every conflict in the family will definitely have a way out when parents choose the right parenting style such as democratic parenting.